(untitled) (KYAMC Journal, 2021)
Background: The clinical diagnosis of stroke in a patient admitted in the intensive care unit (ICU) is undeniably challenging. Several point-based risk scores have been developed to predict clinical outcomes after ischemic stroke. Objective: To assess the Siriraj stroke score and Guy’s Hospital stroke score in the clinical diagnosis of acute stroke. Materials and Methods: All patients were subjected to Computed tomography (CT) scan head within 72 hours of admission. The sensitivity, specificity, positive predictive value was calculated for both the scores. Comparability between the scores and CT scan head finding was determined with the help of Kappa statistic program. Results: Sensitivity of Guy’s Hospital stroke score for ischemic stroke is 100%, specificity is 96.4%, accuracy 97.1%, positive predictive value of 87.5% and negative predictive value 100%. The sensitivity of Guy’s Hospital stroke score for hemorrhage stroke is 96.4%, specificity is 100%, accuracy 97.1%, positive predictive value of 100% and negative predictive value 87.5% Conclusion: Siriraj stroke score as a simple method of screening patients for intracerebral hemorrhage, as it is easier to use at bedside and has a greater accuracy in diagnosing hemorrhage than Guy’s Hospital score. KYAMC Journal. 2021;12(3): 142-146